Teachers' Pedagogical Competence in Finnish Early Childhood Education-A Narrative Literature Review - Samuli Ranta; Jonna Kangas; Heidi Harju-Luukkainen; Tuulikki Ukkonen-Mikkola; Marita Neitola; Jarmo Kinos; Nina Sajaniemi; Arniika Kuusisto (MDPI AG, 2023)
Finnish early childhood education (ECE) is defined in education policies and research as an activity with an emphasis on pedagogy as a holistic and Nordic model of education. Pedagogical competence can be viewed as a special expertise of teachers responsible for the implementation of pedagogy in ECE. However, it is unclear how a teacher's pedagogical competence is defined, understood, and implemented in pedagogical practices and policies. Previous studies define pedagogical competence from different, often narrow, perspectives and various skills have been defined to be a part of teachers' pedagogical expertise. In this study, we aim to take a closer look at how teachers' pedagogical competence is defined in research literature in Finland. As our method, we use a narrative literature review of research papers published between 2010 and 2020. We were able to identify fourteen different definitions of pedagogical competencies that could be categorized into three main categories: (a) meta-competencies, (b) professional competencies, and (c) practical competencies. In summary, we argue that pedagogical competence is often narrowly understood. To implement high-quality ECE, teachers' pedagogical competence should be considered broadly and wholly. Particularly, the shared values and reflection of ethical questions are essential for supporting children's development and learning through holistic education.